Restoration of cellular integrity following “ballistic” pronuclear exchange during Tetrahymena conjugation - Cole, Eric S.; Dmytrenko, Oleksandr; Chmelik, Carl J.; Li, Mark; Christensen, Trenton A.; Macon, Elaine P.; Nilsson, Hannah J.; Blower, Ruth J.; Reuter, Thomas G.; Beckman, John P.; Remmers, Bailey C.; Smith, Claire L.; et al. (Developmental biology, 2018)
During sexual reproduction or conjugation, ciliates form a specialized cell adhesion zone for the purpose of exchanging gametic pronuclei. Hundreds of individual membrane fusion events transform the adhesion zone into a perforated membrane curtain, the mating junction. Pronuclei from each mating partner are propelled through this fenestrated membrane junction by a web of short, cris-crossing microtubules. Pronuclear passage results in the formation of two breaches in the membrane junction. Following pronuclear exchange and karyogamy (fertilization), cells seal these twin membrane breaches thereby re-establishing cellular independence. This would seem like a straightforward problem: simply grow membrane in from the edges of each breach in a fashion similar to how animal cells “grow” their cytokinetic furrows or how plant cells construct a cell wall during mitosis. Serial section electron microscopy and 3-D electron tomography reveal that the actual mechanism is less straightforward. Each of the two membrane breaches transforms into a bowed membrane assembly platform. The resulting membrane protrusions continue to grow into the cytoplasm of the mating partner, traverse the cytoplasm in anti-parallel directions and make contact with the plasma membrane that flanks the mating junction. This investigation reveals the details of a novel, developmentally-induced mechanism of membrane disruption and restoration associated with pronuclear exchange and fertilization in the ciliate, Tetrahymena thermophila. •Tetrahymena thermophila, a ciliate, undergoes complex membrane dynamics during sexual reproduction and pronuclear exchange.•Mating cells initially form a specialized mating junction, where the two plasma membranes adhere.•The adhesion zone undergoes membrane fusion events creating 100s of membrane pores that expand, creating a membrane curtain.•Gamete pronuclei are propelled through this membrane curtain by a meshwork of cris-crossing short microtubules.•Following bilateral nuclear exchange, the junction is restored by an elaborate process of membrane folding and growth.